Thrombopoietin Receptor Agonists: Clinical Use and Evaluation of Treatment Efficacy - A. G. Solodovnikov; E. Yu. Sorokina; E. I. Morkovin (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Idiopathic thrombocytopenic purpura (ITP), or primary immune thrombocytopenia, is an orphan disease associated with thrombocytopenia. One of the most recent and promising approaches to ITP treatment is the use of thrombopoietin receptor agonists (TPO-RAs). The scope of TPO-RA use is expanding rapidly, which stimulates the development of both innovator and generic (or biosimilar) medicines. The aim of the paper was to assess TPO-RA role in ITP treatment, methodological approaches to TPO-RA development, and feasibility of using the platelet count as a pharmacodynamic marker in bioequivalence studies of peptide TPO-RAs in healthy volunteers. Clinical development of new medicines for the treatment of thrombocytopenia includes comparative, parallel-group trials lasting about a year. The standard approach to bioequivalence studies, which is based on the results of comparative pharmacokinetic studies, can be used in marketing authorisation applications for generic non-peptide TPO agonists, while peptide TPO agonists have to comply with specific requirements for biosimilar products. The orphan status of ITP does not affect the development strategy and study design, but it limits the number of patients that could be included into the study. In the absence of valid surrogate biomarkers of efficacy, demonstration of comparable clinical efficacy of the biosimilar and reference drug is usually required in a randomised, parallel, preferably double-blind comparative study. On the other hand, clinical comparability of the biosimilar and reference drug can also be demonstrated in comparative pharmacodynamic studies, if the selected biomarker is a well-established and valid surrogate marker which correlates with patient clinical outcome. Platelet count is a key parameter in both diagnosis of diseases associated with low platelet levels and assessment of treatment efficacy. Therefore, it can be used as a pharmacodynamic marker in bioequivalence studies of biosimilar peptide TPO-RAs. It was concluded that such studies could be performed in healthy volunteers, and not in patients, whose participation in clinical trials is limited due to the orphan status of ITP.